THE STRATEGY OF THE ELECTION SUPERVISORY AGENCY IN THE WEST JAVA REGION IN INCREASING COMMUNITY PARTICIPATORY SUPERVISION - Hendra Setiadi; Mala Sondang Silitonga; Edy Sutrisno (DIA: Jurnal Administrasi Publik, 2023)
Community participation is an indicator that determines the quality of election administration and signifies the importance of democracy for a country. Participation in elections is carried out in two ways, including first conducting election socialization and secondly carrying out voter education and conveying the results of election monitoring and reporting suspected election violations. High public participation in elections (voter turnout) and public trust are part of the integrity of elections on the other hand low participation in elections is associated with public apathy. The Bawaslu’s data for the 2019 simultaneous elections in the West Java region show high findings and reports of violations, while public participation in monitoring and reporting suspected violations is considered low. The low level of public involvement in monitoring and reporting electoral fraud is due to the lack of socialization and education carried out by Bawaslu, so the capacity of the community as a human resource to monitor and report suspected election violations is still low. The research method used is a qualitative research method with research instruments including interviews with 17 key informants and field observations by making direct observations covering the West Java region and reviewing documents as supporting data in data refinement. The study results illustrate that the Participatory Oversight Program implemented by Bawaslu could have been more optimal, as evidenced by the low level of public participation in election monitoring and reporting suspected violations. In contrast, future election violations are increasingly massive. So it requires strategies and collaboration to increase participatory community supervision.